Screening diagnostic candidates for schistosomiasis from tegument proteins of adult Schistosoma japonicum using an immunoproteomic approach. - Min Zhang; Zhiqiang Fu; Changjian Li; Yanhui Han; Xiaodan Cao; Hongxiao Han; Yantao Liu; Ke Lu; Yang Hong; Jiaojiao Lin (PLoS Neglected Tropical Diseases)
Background Schistosomiasis is one of the world's most prevalent zoonotic diseases and a serious worldwide public health problem. Since the tegument (TG) of Schistosoma japonicum is in direct contact with the host and induces a host immune response against infection, the identification of immune response target molecules in the schistosome TG is crucial for screening diagnostic antigens for this disease. Methodology/principal findings In this study, an immunoproteomics approach used TG proteins as screening antigens to identify potential diagnostic molecules of S. japonicum. Ten spots corresponding to six proteins were identified that immunoreacted with sera from S. japonicum-infected rabbits but not sera from uninfected rabbits and their specific IgG antibody levels declined quickly after praziquantel treatment. Recombinant phosphoglycerate mutase (PGM) and UV excision repair protein RAD23 homolog B (RAD23) proteins were expressed and their diagnostic potential for schistosomiasis was evaluated and compared with schistosome soluble egg antigen (SEA) using ELISA. The results showed high sensitivity and specificity and low crossreactivity when rSjPGM-ELISA and rSjRAD23-ELISA were used to detect water buffalo schistosomiasis. Moreover, antibodies to rSjPGM and rSjRAD23 might be short-lived since they declined quickly after chemotherapy. Conclusion/significance Therefore, the two schistosome TG proteins SjPGM and SjRAD23 were identified as potential diagnostic markers for the disease. The two recombinant proteins might have the potential to evaluate the effectiveness of drug treatments and for distinguishing between current and past infection.